COVID-19 in Pediatric Patients With Acute Lymphoblastic Leukemia or Lymphoma - Saman K. Hashmi; Jessica Bodea; Tushar Patni; Savannah Angel; Nickhill Bhakta; Sima Jeha; Seth E. Karol; Raul C. Ribeiro; Jeffrey E. Rubnitz; Joshua Wolf; Yimei Li; Ching‐Hon Pui; et al. (2024)
Importance COVID-19 in pediatric patients with acute lymphoblastic leukemia or lymphoma (ALL/LLy) has not been described in detail and may affect chemotherapy administration and long-term outcomes. Objective To describe the clinical presentation of COVID-19 and chemotherapy modifications in pediatric patients with ALL/LLy. Design, Setting, and Participants This is a retrospective case series of patients at St Jude Children’s Research Hospital and its affiliate sites with newly diagnosed ALL/LLy who were treated on the Total XVII protocol (NCT03117751) between March 30, 2020, and June 20, 2022. Participants included patients aged 1 to 18 years who were receiving protocol chemotherapy. Acute symptoms and chemotherapy modifications were evaluated for 60 days after the COVID-19 diagnosis, and viral clearance, adverse events, and second SARS-CoV-2 infections were followed up during the 27-month study period. Exposures SARS-CoV-2; all patients were screened at least weekly and at symptom onset and/or after known exposure to SARS-CoV-2. Main Outcomes and Measures Description of the spectrum of COVID-19 illness and chemotherapy modifications. Results Of 308 pediatric patients, 110 (36%) developed COVID-19 at a median age of 8.2 (IQR, 5.3-14.5) years. Sixty-eight patients (62%) were male. Most patients were in the continuation/maintenance phase of chemotherapy (101 [92%]). Severe disease was rare (7 [6%]) but was associated with older age, higher white blood cell counts at ALL/LLy diagnosis, lower absolute lymphocyte counts at COVID-19 diagnosis, abnormal chest imaging findings, and SARS-CoV-2 reinfection. Rare but serious thrombotic events included pulmonary embolism and cerebral venous sinus thrombosis (n = 1 for each). No multisystem inflammatory syndrome in children or death was seen. SARS-CoV-2 reinfection occurred in 11 patients (10%) and was associated with older age and with receiving standard or high-risk vs low-risk ALL/LLy therapy. Chemotherapy interruptions occurred in 96 patients (87%) and were longer for patients with severe disease, SARS-CoV-2 reinfection, and/or a COVID-19 diagnosis during the pre-Omicron variant period vs the post-Omicron period (after December 27, 2021). Conclusions and Relevance In this case series of COVID-19 in pediatric patients with ALL/LLy, severe COVID-19 was rare, but chemotherapy administration was affected in most patients. Long-term studies are needed to establish the outcomes of COVID-19 in this population.